Integrasi Kurikulum Pendidikan Islam Anak Usia Dini dan Pendidikan Agama Islam untuk Meningkatkan Literasi Keagamaan Anak Prasekolah - Ziliwu, Yusman; Sahyan, Sahyan (AUD Cendekia: Journal of Islamic Early Childhood Education, 2025)
This study aims to analyze the integration of the Early Childhood Islamic Education (PIAUD) curriculum and the Islamic Religious Education (PAI) curriculum in shaping religious literacy and Islamic social behavior among preschool children at RA Al-Habib. Using a qualitative phenomenological approach, the study explores the experiences of teachers, the principal, and parents regarding curriculum integration practices, strategies for cultivating Islamic social habits, as well as supporting and inhibiting factors that influence the formation of children’s religious behavior. The findings reveal that collaboration between PIAUD and PAI teachers serves as the main foundation of the integration, reflected in the planning, implementation, and evaluation of learning activities. Habit-formation strategies are carried out through daily Islamic rituals, teacher modeling, moral storytelling, cooperative play, and reflective dialogues that gradually instill socio-religious values. Supporting factors include institutional commitment, teacher competence, a religious learning environment, and family support, while inhibiting factors consist of variations in children’s initial abilities, limitations in integrative instructional design, restricted learning time, and the lack of age-appropriate learning materials. This study contributes to enriching the theory of PIAUD–PAI curriculum integration with empirical evidence and offers practical recommendations for developing holistic, contextual, and effective religious learning models in Islamic early childhood education institutions.